Determinants of early cessation of exclusive breastfeeding practices among rural mothers from Jaffna District of Sri Lanka - Kandeepan Karthigesu; Sandrasegarampillai Balakumar; Vasanthy Arasaratnam (BMC, 2023)
Abstract Background Sri Lanka is an upper-middle-income country with excellent health statistics. However, 2016 Demographic and Health Survey data have shown 82% and 64% of mothers exclusively breastfed infants aged 0-6 months and 4-5 months, respectively. The short duration of exclusive breastfeeding (EBF) has an impact on the growth and development of babies. Since no studies have been reported on EBF practices of the rural mothers in Jaffna District, an administrative district among 25 districts of Sri Lanka, this study aimed to assess the factors influencing the early cessation of EBF. Methods For this community-based cross-sectional study, 338 mother-child pairs were selected from 2013-14. EBF was defined as children not receiving any food or drink, including complementary foods, formula milk or milk products except for medicines and vitamins or mineral drops, other than breast milk since birth. Socio-economic and demographic factors, the influence of the mode of delivery, and knowledge on EBF were obtained using an interviewer-administered questionnaire. The details of EBF and reasons for the cessation of breastfeeding before six months were obtained from a subgroup of mothers (n = 208). Multivariate analysis was performed to explore the correlates of breastfeeding. Results In this study, 71.2% (95% CI 64.5, 77.2) had practiced EBF for six months. Early discontinuation of EBF was practiced by employed mothers (AOR 4.3; 95% CI 1.3, 13.9), mothers of low birth weight babies (AOR 3.6; 95% CI 1.6, 8.2) and those who experienced Cesarean section birth (AOR 2.9; 95% CI 1.2, 6.9). The EBF practiced by mothers of rural Jaffna was not associated with the gender of the babies, type of family, number of children in a family, religion of the household, knowledge on EBF, or family income. Conclusion The prevalence of EBF up to six months was low in rural Jaffna, and it was influenced by employment, birthweight of the babies, and the mode of delivery. To enhance EBF, the Regional Directorate of Health Service, Jaffna, should take necessary action with policymakers to increase maternity leave for at least six months, reduce the Cesarean section rate, and provide nutritional support to pregnant mothers.